18th Annual Computer Security Applications Conference, 2002. Proceedings.
DOI: 10.1109/csac.2002.1176299
|View full text |Cite
|
Sign up to set email alerts
|

Gender-preferential text mining of e-mail discourse

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 12 publications
0
66
0
1
Order By: Relevance
“…Among the better known of these are Yule's K-measure (1944), Sichel's S-measure (1975), and Honore's Rmeasure (1979). Ultimately, none of these measures has proved especially useful on its own Grieve 2007), though it may be that these features have marginal value as additional inputs together with the features that we consider below (De Vel et al 2001;Corney et al 2002;Abbasi & Chen 2005;Zheng et al 2006;Li et al 2006;Abbasi & Chen 2008).…”
Section: Complexity Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the better known of these are Yule's K-measure (1944), Sichel's S-measure (1975), and Honore's Rmeasure (1979). Ultimately, none of these measures has proved especially useful on its own Grieve 2007), though it may be that these features have marginal value as additional inputs together with the features that we consider below (De Vel et al 2001;Corney et al 2002;Abbasi & Chen 2005;Zheng et al 2006;Li et al 2006;Abbasi & Chen 2008).…”
Section: Complexity Measuresmentioning
confidence: 99%
“…Finally, for documents such as email, blogs and other online content, formatting and other structural features can also be profitably exploited for authorship attribution (De Vel et al 2001;Corney et al 2002;Abbasi & Chen 2008).…”
Section: Other Specialized Featuresmentioning
confidence: 99%
“…Researchers have also attempted to automatically predict the gender of email senders using supervised learning techniques based on linguistic features (Corney et al, 2002;Cheng et al, 2011;Deitrick et al, 2012), a task we do not address in this paper. These studies use datasets that are relatively smaller in size.…”
Section: Related Workmentioning
confidence: 99%
“…These studies use datasets that are relatively smaller in size. Corney et al (2002) use around 4K emails from 325 gender identified authors. Cheng et al (2011) use around 9K emails from 108 gender identified authors.…”
Section: Related Workmentioning
confidence: 99%
“…Starting from the surfacial properties, we measure the sentence, utterance and word length, including the proportion of words shorter than 4 or longer than 6 letters, frequency of each punctuation mark, 5 https://wordnet.princeton.edu/man/ lexnames.5WN.html 6 For complete overview refer to www.liwc.net and endings of each adjective as per Corney et al (2002). On the syntax level we measure the frequency of each part of speech as well as the 500 most frequent part-of-speech bi-, tri-and quadrigrams, and the frequency of each dependency obtained from the Stanford Parser.…”
Section: Classification Approach For Direct Speechmentioning
confidence: 99%